2000
DOI: 10.1038/sj.gt.3301179
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory action of type I interferons deduced from mice expressing interferon β

Abstract: Type I interferons (IFN) are widely used for the therapeutic treatment of viral infections, tumor growth and various chronic diseases such as multiple sclerosis. Antagonism between type I IFNs and IFN-␥ has been described in cells of the immune system, in particular in the activation of macrophages. To study the systemic effects of type I IFNs we used transgenic mice carrying a human IFN-␤ (hIFN-␤) gene under the control of the rat insulin I promoter. These animals expressed high levels of hIFN-␤ in ␤-pancreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 59 publications
(70 reference statements)
2
14
0
Order By: Relevance
“…Similarly, it has been shown to inhibit monocyte migration across human brain-derived endothelial cells (Seguin et al, 2003) and reduce cellular infiltration into damaged brain regions (Veldhuis et al, 2003b). On a cellular level, IFNβ has been shown to reduce reactive oxygen species (Lopez-Collazo et al, 1998, Stewart et al, 1998, Hua et al, 2002), suppress inflammatory cytokine production and induce IL-1Ra (Bosca et al, 2000, Palmer et al, 2004), promote nerve growth factor production by astrocytes (Boutros et al, 1997) and protect neurons from toxicity induced by activated microglia (Jin et al, 2007). In addition, systemic administration of IFNβ has been shown to reduce infarct damage in rat and rabbit models of ischemic stroke (Liu et al, 2002, Veldhuis et al, 2003a).…”
Section: Mechanisms Of Neuroprotection—reprogramming Tlr Signalingmentioning
confidence: 99%
“…Similarly, it has been shown to inhibit monocyte migration across human brain-derived endothelial cells (Seguin et al, 2003) and reduce cellular infiltration into damaged brain regions (Veldhuis et al, 2003b). On a cellular level, IFNβ has been shown to reduce reactive oxygen species (Lopez-Collazo et al, 1998, Stewart et al, 1998, Hua et al, 2002), suppress inflammatory cytokine production and induce IL-1Ra (Bosca et al, 2000, Palmer et al, 2004), promote nerve growth factor production by astrocytes (Boutros et al, 1997) and protect neurons from toxicity induced by activated microglia (Jin et al, 2007). In addition, systemic administration of IFNβ has been shown to reduce infarct damage in rat and rabbit models of ischemic stroke (Liu et al, 2002, Veldhuis et al, 2003a).…”
Section: Mechanisms Of Neuroprotection—reprogramming Tlr Signalingmentioning
confidence: 99%
“…It is a type I interferon (IFN), which includes IFN alpha (IFNA), IFN beta (IFNB), IFN delta (IFND), and IFN omega (IFNW). After binding to a common receptor, IFNA receptor 1 (IFNAR1), and IFNAR2, type I IFNs affect the production of inflammatory cytokines such as interleukin- (IL-) 1 β and tumor necrosis factor α (TNF- α ) [6, 7]. Thus, type I IFNs have widely recognized roles in inflammatory diseases, such as experimental allergic encephalomyelitis, multiple sclerosis, and spontaneous autoimmune diabetes [5, 810].…”
Section: Introductionmentioning
confidence: 99%
“…8 The mechanism by which IFN-␤ mediates these contrasting effects on Th1 cell generation operates, at least in part, by regulating DC expression of interleukin-12 (IL-12) family cytokines. Bosca et al 9 showed in mice that systemic administration of IFN-␤ might influence the response to proinflammatory stimuli, in particular Th1 cell-derived cytokines, through antagonism of IFN-␥ signaling.…”
Section: Introductionmentioning
confidence: 98%